POSSIBILITIES OF OVARIAL SUPPRESSION IN HORMONE-DEPENDENT MAMMARY GLAND CANCER - I. A. KOROLEVA; M. V. KOPP (Медицинский совет, 2017)
Ovarian suppression (OS) is an effective therapy in hormone-sensitive breast cancer. Oophorectomy and ovarian irradiation have historically been used to achieve the goal of ovarian ablation. Luteinizing hormone releasing hormone (LHRH) analogues have largely supplanted surgical and radiation-based approaches because of less side effects and a lower likelihood of permanent amenorrhea, with the potential for restoration of fertility. LHRH analogues goserelin, buserelin, leuprorelin are equally effective. Buserelin is economically attractive.